2007
DOI: 10.1073/pnas.0709096104
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutation in a mucolipin transient receptor potential channel leads to melanocyte loss in varitint–waddler mice

Abstract: Transient receptor potential (TRP) genes of the mucolipin subfamily (TRPML1-3 and MCOLN1-3) are presumed to encode ion channel proteins of intracellular endosomes and lysosomes. Mutations in human TRPML1 (mucolipin 1/MCOLN1) result in mucolipidosis type IV, a severe inherited neurodegenerative disease associated with defective lysosomal biogenesis and trafficking. A mutation in mouse TRPML3 (A419P; TRPML3 Va ) results in the varitint-waddler (Va) phenotype. Va mice are deaf, exhibit circling behavior due to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
302
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(322 citation statements)
references
References 20 publications
(37 reference statements)
14
302
2
Order By: Relevance
“…The cells were sequentially perfused with solutions containing 140 or 0 mM Na þ , as indicated by the dark and light grey bars. Almost all TRP channels function as non-selective, Ca 2 þ -permeable channels (Pedersen et al, 2005;Nilius et al, 2007), and TRPML3(A419P) is permeable to Ca 2 þ (Grimm et al, 2007) and conducts Ca 2 þ at isotonic extracellular Ca 2 þ (Ca 2 þ o ) (Xu et al, 2007). Notably, Figures 1D (Owsianik et al, 2006), indicating that TRPML3 is a Ca 2 þ channel that is also permeable to monovalent cations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were sequentially perfused with solutions containing 140 or 0 mM Na þ , as indicated by the dark and light grey bars. Almost all TRP channels function as non-selective, Ca 2 þ -permeable channels (Pedersen et al, 2005;Nilius et al, 2007), and TRPML3(A419P) is permeable to Ca 2 þ (Grimm et al, 2007) and conducts Ca 2 þ at isotonic extracellular Ca 2 þ (Ca 2 þ o ) (Xu et al, 2007). Notably, Figures 1D (Owsianik et al, 2006), indicating that TRPML3 is a Ca 2 þ channel that is also permeable to monovalent cations.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the native TRPML3 is found in unidentified vesicular compartments and in the stereocilia outer membrane in the hair cells of the cochlea (Di Palma et al, 2002). All the groups that reported the function of TRPML3(A419P) found that, similar to the native TRPML3, recombinant TRPML3 is expressed at the plasma membrane and intracellular vesicles (Grimm et al, 2007;Kim et al, 2007;Xu et al, 2007;Nagata et al, 2008). The report that TRPML3 is expressed exclusively in the endoplasmic reticulum (Venkatachalam et al, 2006) is probably the result of mistargeting of the channel due to masking of C-terminal targeting motifs (Song et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, the extracellular side is equivalent to the luminal side of TRPML1 in endo/lysosomes. The constitutively active V432P mutant, equivalent to the gain-of-function mutation of the mouse TRPML3 in the varitint-waddler ( va ) phenotype 15,27-29 , can be trafficked to the plasma membrane without replacing the di-leucine motifs and therefore V432P and V432P/D472N mutants were both constructed on the background of the wild type channel. The N-terminus truncation mutant was constructed on the background of MmTRPML1-4A.…”
Section: Methodsmentioning
confidence: 99%
“…Four linker helices surround the S6 bundle crossing and stabilize the closed channel pore. It is interesting to note that several gain-of-function mutations similar to the V432P varitint-waddler phenotype 15,27-29 have been identified on S5 in a proline-scanning mutagenesis study 30 , including R427P, C430P and C431P, which are all clustered at the interaction interface between the S5 and S4-S5 linker (Fig. 4c).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation